Harvard business essentials coaching and mentoring - Harvard Business School (Boston Harvard Business School Press, 2004)
Effective managers know that timely coaching can dramatically enhance their teams' performance.
Includes bibliographical references (p. 149-152)
Keywords: Mentoring in business